Pañjābī sāhitta dā sarota-mūlaka itihāsa - Jaggi, Rattan Singh (Pabalīkeshana Biūro, Pañjābī Yūnīwarasiṭī, 1998)
History of Panjabi literature, from its origin to date
v. 1. [without special title] – v. 2. Pūrawa maddhakāla-1 – v. 3. Pūrawa maddhakāla-2 – v. 4. Maddha-kala-3
Keywords: Panjabi literature